Risk assessment in system of small businesses crisis management - Ugrimovа, Iryna; Kraivska, Inna; Gryshchenko, Anna (Приазовський державний технічний університет, 2016)
The paper deals with anticrisis management of enterprises in the conditions of significant influence of external factors. Anticrisis management system, the core of which is risk assessment in economic entities activity is considered. The state of small business and negative influence of outer environment changes on enterprises financial outcomes have been examined. Existing techniques of anticrisis financial management diagnostics, which often do not take into account sectoral characteristics and the size of an enterprise have been evaluated. The author's technique of an integral index of financial risk calculation has been proposed. Formation of an informative indexes system and the mechanism of their implementation, the hierarchies of a financial ratios system based on their factors loading, objectively reflecting both sectoral specific features of businesses and peculiarities of their financial activity, necessary for quantitative risk assessment of small businesses have been used in the process of the technique development. Gradation of a financial risk level, its qualitative evaluation and assessment of crisis level using a certain scale have been proposed. An algorithm for integral assessment of financial risk calculating has been formed. Proposed technique for assessing enterprises financial risk level will allow to identify the priorities for financial management of small businesses and prevent intensification of crisis processes. It takes into account the dynamics of internal financial processes, allows for monitoring and forecasting the magnitude of risk, has objective nature; its relationship with analytical and management processes is of utmost importance and urgency. Proposed technique is a key instrument for financial risk operational monitoring of a financial risk level and diagnosing of the basic problem situations using Ехеl program.

У статті розглянуто питання антикризового управління підприємствами в умовах значного впливу зовнішніх факторів. Розглядається система антикризового управління, стрижнем якої є оцінка ризику в діяльності суб’єктів господарювання. Розглянуто стан малого бізнесу і вплив змін зовнішнього середовища, що негативно відображається на формуванні фінансових результатів підприємств. Оцінено діючі методики діагностики антикризового фінансового управління, які часто не враховують галузеві особливості і розмір підприємства. Запропоновано авторську методику інтегрального показника фінансового ризику. В розробці методики використовувалось формування системи інформативних ознак та механізм їх реалізації, ієрархії системи фінансових коефіцієнтів з врахуванням їх факторних навантажень, яка об’єктивно відображає як галузеву специфіку підприємств, так і особливості їх фінансової діяльності та необхідна для кількісної оцінки ризику підприємств малого бізнесу. Показано градацію рівня фінансового ризику і його якісну оцінку та оцінку рівня кризовості за певною шкалою. Складено алгоритм розрахунку інтегральної оцінки фінансового ризику. Пропонована методика оцінки рівня фінансового ризику підприємств дозволить виявити пріоритети управління фінансами підприємств малого бізнесу і запобігти активізації кризових процесів. Вона враховує динаміку розвитку внутрішніх фінансових процесів, дозволяє проводити моніторинг і прогнозування величину ризику, має об’єктивний характер; її взаємозв’язок з аналітичними і управлінськими процесами набуває виняткового значення і актуальності. Пропонована методика є ключовим інструментом оперативного моніторингу рівня фінансового ризику та діагностики основних проблемних ситуацій з використанням програми Ехеl.
Оцінка ризику в системі антикризового управління підприємствами малого бізнесу
Keywords: small business; crisis management; financial ratios; risk assessment; integral index; management priorities; бізнес малий; управління антикризове; коефіцієнти фінансові; оцінка ризику; показник інтегральний; пріоритети управління